The Role of Organizational Agility, Perceived Support, and Culture in Shaping Social Sustainability - Januari Ayu Fridayani; Stephanus Eri Kusuma (Jurnal Organisasi dan Manajemen, 2024)
Purpose – The objective of this study is to evaluate the influence of organizational agility on social sustainability, organizational support, and organizational culture in credit union cooperatives. Furthermore, it examines how organizational support and organizational culture influence the connection between organizational agility and social sustainability. Methodology – The study adopted a quantitative methodology, utilizing questionnaires distributed to 173 people associated with credit union (CU) Angudi Laras and credit union (CU) Lestari. The data analysis was performed with Partial Least Squares (PLS) methodology, employing Smart PLS 3.0 software. The study comprises the research design, data gathering methods, scheduling, and intervention sequence. Findings – The results demonstrate a substantial and direct influence of organizational agility on organizational support, organizational culture, and social sustainability. The study emphasizes significant and positive results, which are substantiated by diagrams, graphs, and tables that depict the research findings. Originality – This study enhances the understanding of the social aspect of sustainability in credit union cooperatives by highlighting the impact of organizational agility, organizational support, and organizational culture. This study explores the impact of organizational support and organizational culture on organizational agility and social sustainability.